Effect of Dietary Supplements of Bypass Fat containing Omega-3 Fatty Acids on Productive Performance and Milk Fatty Acid Profile of Lactating Cows - Guntanapreeda, Lalita; Buaphan, Sirirat (Journal of Mahanakorn Veterinary Medicine, 2023)
Bypass fat supplementation which is the source of omega-3 fatty acids in dairy cows is a great way to improve the nutritional value for consumers. The aim of the experiment was to determine the effect of bypass fat containing omega-3 fatty acids supplementation on milk yield, compositions, milk fatty acid profiles and blood metabolites of lactating dairy cows. Eight crossbred cows (>87.5% Holstein Friesian), averaging 62.50 ± 26.11 days in milk were analyzed using the paired t-test. The first period (CON) cows were fed a basal diet based on concentrate containing 16% of crude protein, soybean milk residue and roughage source (sweet corn husk and cob silage and Napier grass). The second period cows were fed the same diets of CON and supplemented with 200 g/h/d of bypass fat (BF). The experiment was conducted for 8 weeks with 14 days for adaptation. Supplementation of bypass fat had no negative effect on dry matter intake and milk yield (P>0.05). Milk compositions were not affected by BF (P<0.05). However, blood glucose concentration was increased in BF (P<0.01), but there were decreased in NEFA and triglyceride concentration (P<0.05). In addition, concentration of milk omega-3 fatty acids and unsaturated fatty acids were increased by BF supplementation (P>0.05). This study indicates that supplementation of bypass fat containing omega 3 fatty acids can positively impact on energy balance and milk fatty acid profiles of lactating cows.